Jogos reduzidos no basquetebol : influência da quantidade de jogadores, tamanho da quadra e utilização do coringa no desempenho tático-técnico de jovens jogadores - Souza, Walber Jose Figueiredo de (2024)
Small-sided games (SSGs) are an effective methodological alternative for enhancing athletic performance, as they allow for the integrated development of physical, tactical, and technical aspects. SSGs are characterized by changes to the functional structures of formal games, including changes in playing area size, number of players, rules, action limitations, tactical strategies, rest intervals, and other adjustments. These manipulations in SSGs impact performance from different perspectives. Thus, altering the number of players and court size in numerically uneven formats can influence the tactical and technical performance of young basketball players. This master's thesis aimed to analyze the tactical behavior and technical skills of young basketball players by altering the number of players (numerical equality and inequality), with and without the use of a wildcard player, and varying the size of the playing area (official and reduced court). The sample consisted of young male basketball players aged 12 to 16, selected through convenience sampling. Initially, a demographic data questionnaire was administered, followed by SSGs with various modifications. Analyses were conducted using the Game Performance Assessment Instrument (GPAI), which evaluates offensive and defensive actions and assess the intentionality of technical and tactical actions. This master's thesis is structured into two experimental articles derived from the specific objectives of the study. The first article was developed to examine tactical behavior, decision-making, and technical skills of young novice basketball players in SSGs with varying numerical configurations and court sizes. The participants were 16 male novice players, aged between 11 and 15 years, with no competitive experience. Thirteen games were played, encompassing nine formats of SSGs with numerical equality, superiority, and inferiority, on two court sizes: full court (FC) and half court (HC). Passing effectiveness was significantly higher (p < 0.05) in 5 vs. 4 and 4 vs. 3, while dribbling effectiveness was significantly higher (p < 0.05) in 2 vs. 1 HC. The 3 vs. 3 FC format showed higher (p < 0.05) shooting effectiveness. Reception and rebounding effectiveness were both significantly higher (p < 0.05) in 2 vs. 1 HC. However, the number of appropriate passes was significantly fewer (p < 0.05) in 4 vs. 3 FC. Dribbling effectiveness was significantly higher (p < 0.05) in 2 vs. 1 HC, and appropriate shots were also significantly higher (p < 0.05) in 2 vs. 1 HC. In terms of defensive and offensive technical and tactical actions, 3 vs. 3 HC showed significantly higher values (p < 0.05) of support, while ball marking was significantly higher (p < 0.05) in 3 vs. 2 HC. The second article was analyzed the influence of scoring and non-scoring wildcard players on the tactical performance of young basketball players, conducted with numerical inequality on two court sizes. Twenty-eight games lasting 3 minutes each were played, and players having a 10-minute rest interval between game. Skill execution analyses indicated significant differences for appropriate shots (p = 0.001; w = 0.365). Post hoc analyses revealed significantly more appropriate shooting actions in the 3 vs. 2 game format with a non-scoring wildcard player compared to the 4 vs. 3 format with a scoring wildcard player (p = 0.008; r = 0.804) and the 4 vs. 3 format with a non-scoring wildcard player (p = 0.045; r = 0.668). Tactical behavior analyses revealed differences in support actions (p = 0.001; w = 0.51), coverage (p = 0.001; w = 0.544) and marking the player with the ball (p = 0.041; w = 0.172). Specifically, support actions were more frequent in the 4 vs. 3 (p = 0.003; r = 0.873) and 3v2 (p = 0.001; r = 1.078) formats with a non-scoring wildcard player compared to the 4 vs. 3 format with a scoring wildcard player. Based on the results of this master's thesis, it is concluded that smaller SSGs formats (balanced and unbalanced) tend to increase the frequency, effectiveness, and appropriateness of offensive and defensive behaviors, particularly those involving direct actions. Furthermore, the presence of a scoring wildcard player impacted technical and tactical performance in FC formats, while the non scoring wildcard player had a greater impact in HC formats.